Altered Executive Function in Suicide Attempts - J. Fernández; S. Alberich; I. Zorrilla; I. González-Ortega; M.P. López; V. Pérez-Solà; E. Vieta; A.M. González-Pinto; P.A. Saiz (European Psychiatry, 2022)
Introduction Executive function organizes and directs behaviour but alterations in this cognitive domain can lead to inaccurate perception, interpretation and response to environmental information, which could be a risk factor for suicide.